Development Quizizz Application As Instrument Evaluation in Arabic Language Learning at Madrasah Aliyah - Jamhuri, Wirawan; Kasih, BQ. Widia Nita (Nurul Jadid University, 2024)
In response to the need for effective and interactive evaluation tools in Arabic language learning, this study aims to develop a Quizizz-based evaluation instrument for use at the Madrasah Aliyah level, employing the ADDIE instructional design model. The research involves a comprehensive process including needs analysis, item development aligned with curriculum standards, validation by content and media experts, limited trials with students, and product evaluation. Expert validation indicates a high level of content accuracy and media effectiveness, while feedback from teachers and students confirms the instrument’s practicality and ease of implementation. The results also highlight the application’s advantages in facilitating fast, accurate, and engaging assessments. Although the development faced several challenges, such as limited technological infrastructure and user proficiency, it was supported by strengths including the platform’s user-friendly design, interactive features, and efficiency in generating instant feedback. This study contributes to Arabic language pedagogy by integrating digital innovation into formative assessment practices suitable for faith-based and resource-limited educational environments.